Otomasi Sistem Pengolahan Air Hujan Berbasis Arduino Uno : Otomasi Sistem Pengolahan Air Hujan Berbasis Arduino Uno - Purbhadi, Ignatius Agus (ReTII, 2022)
Indonesia is a tropical area that has quite high rainfall. However, there are some areas that lack clean water for consumption as drinking due to unfavorable geographical conditions, one of which is in Tempursari Hamlet, Sleman Regency, Yogyakarta. The abundant rainwater in the village is treated and used for drinking water. The Tempursari Hamlet community treats rainwater using a conventional electrolysis system that requires an operator in its operating system. This research aims to design an automated system for processing rainwater into water suitable for consumption. The conventional rainwater treatment system is modified into an automatic system using Arduino Uno control. The method used is to find supporting data in the form of determining system time, designing control systems, making programs and testing. The design of the automation carried out by the Arduino Uno controller is to pump water from the rainwater reservoir to the electrolysis vessel for rainwater processing. Rainwater that has met the requirements for a pH level of 7.5 (alkaline) from the results of electrolysis is automatically distributed to ready-to-drink water reservoirs through distribution pumps, while acidic waste water is distributed to waste collections through a disposal pump. The results of the tests carried out on a water treatment unit with a capacity of 30 liters, the filler pump took 18 minutes to fill the electrolysis vessel, the electrolysis process took 12 hours to increase the pH of the water from 6.4 to 7.5. The process of distributing ready-to-drink water and disposing of waste water takes 9 minutes. The entire process needed for rainwater treatment is then used as a timer for the Arduino Uno control system program. Testing of the automation system has been carried out and is running as needed so as to provide convenience for processing rainwater automatically until it is suitable for consumption.